Fetal tricuspid annular plane systolic excursion (f‐TAPSE): evaluation of fetal right heart systolic function with conventional M‐mode ultrasound and spatiotemporal image correlation (STIC) M‐mode. (26th July 2013) - Messing, B.; Gilboa, Y.; Lipschuetz, M.; Valsky, D. V.; Cohen, S. M.; Yagel, S.
ABSTRACT Objectives Fetal tricuspid annular plane systolic excursion (f‐TAPSE) is a modified method to measure the vertical movement of the tricuspid valve annulus by M‐mode ultrasound, in order to assess the fetal right heart. Evaluation of right heart function is well‐recognized in pediatric and adult cardiology, but has not been studied widely in the fetus. We aimed to study f‐TAPSE in the second half of gestation in normal fetuses, to establish reference ranges for this measure, to evaluate the usefulness of spatiotemporal image correlation (STIC) M‐mode in obtaining it, and to compare conventional M‐mode and STIC M‐mode‐based measures of f‐TAPSE. Methods We recruited gravidae presenting to our centers from 20 to 38 weeks for targeted organ scans, fetal echocardiography or third‐trimester fetal surveillance, with structurally normal singleton fetuses and verified gestational age (GA). Because of the small number of subjects at the lower limit, fetuses at 20 and those at 21 weeks were combined into a single group ('21 weeks'). During the booked scan, in addition to standard biometry, M‐mode was applied to the tricuspid annulus, parallel to the ventricular septum, and the amplitude of the resulting wave was measured. To allow comparison with STIC M‐mode, a STIC volume was acquired and saved. In post‐processing, the volume was rotated to show an apical four‐chamber view, and f‐TAPSE was investigated in a similar fashion to that used for conventional M‐mode. Two to three measures of TAPSE were taken and the results averaged. In thirty women, measurements were performed by two observers and inter‐ and intraobserver variation were calculated. Results We examined 341 fetuses at GA 20–39 weeks. Conventional M‐mode f‐TAPSE values ranged from a mean of 3.6 (± 1.1) mm at 21 weeks to a mean of 8.6 (± 1.5) mm at 39 weeks. In 45 cases we were unable to perform conventional M‐mode ultrasound because of fetal lie; in eight cases STIC volumes were found in post‐processing to be unsuitable for analysis. STIC f‐TAPSE values ranged from a mean of 4.2 (± 1.4) mm at 21 weeks to a mean of 8.3 (± 1.5) mm at 39 weeks. Scatterplots of f‐TAPSE measures obtained with conventional M‐mode and with STIC M‐mode were created vs GA and estimated fetal weight (EFW). For both modalities, f‐TAPSE increased linearly with GA and with EFW. Good correlation was found between the two methods (Pearson's R2 = 0.904). No significant difference was found in mean or variance of the distributions or slopes of the regression equations. Inter‐ and intraobserver variation (intraclass correlation coefficient) in conventional M‐mode and STIC M‐mode f‐TAPSE measures were 0.94 and 0.97, respectively. Conclusion F‐TAPSE in normal fetuses increases over the course of gestation and correlates to EFW. F‐TAPSE measurement is easy to perform and available on all ultrasound machines; STIC f‐TAPSE is possible on machines with STIC capability and produces similar measures with a greater success rate. We suggest the addition of f‐TAPSE measurement to fetal right cardiac function evaluation. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.